Metagenome association study of the gut microbiome revealed biomarkers linked to chemotherapy outcomes in locally advanced and advanced lung cancer - Zhe Zhao; Kailun Fei; Hua Bai; Zhijie Wang; Jianchun Duan; Jie Wang (Thoracic Cancer)
Background The gut microbiome is important in the development and immunotherapy efficacy of lung cancer. However, the relationship between the intestinal flora and chemotherapy outcomes remains unclear and was investigated in this study. Methods We analyzed baseline stool samples from patients with locally advanced and advanced lung cancer before chemotherapy treatment, through metagenomics of the gut microbiota. The composition, diversity, function, and metabolic pathway analysis were compared among patients with different clinical outcomes. Results From 64 patients, 33 responded to treatment (responders) and 31 did not (nonresponders). Streptococcus mutans and Enterococcus casseliflavus were enriched in responders (P < 0.05), while 11 bacteria including Leuconostoc lactis and Eubacterium siraeum were enriched in nonresponders (P < 0.05) by variance analysis. Responders were associated with significantly higher Acidobacteria and Granulicella, while Streptococcus oligofermentans, Megasphaera micronuciformis, and Eubacterium siraeum were more abundant in nonresponders by Lefse analysis. Streptococcus mutans and Enterococcus casseliflavus were further identified as bacterial markers relevant to responders using unsupervised clustering, and Leuconostoc lactis and Eubacterium siraeum were related to nonresponders. The L‐glutamate degradation VIII pathway was enriched in responders (P = 0.014), and the C4 photosynthetic carbon assimilation cycle, reductive TCA cycle I, and hexitol fermentation to lactate, formate, ethanol, and acetate were enriched in nonresponders (P < 0.05). Additionally, significant associations of bacterial species with clinical phenotypes were observed by Spearman correlation analysis. Conclusions The specific gut microbiome of patients with lung cancer might be connected to the clinical outcomes of chemotherapy. Key points Significant findings of the study Lung cancer patients with different gut microbiome compositions and microbiome metabolic pathways have different responses to chemotherapy. Microbiome species are also associated with different lung cancer clinical phenotypes. What this study adds We have identified specific gut microbiome species that can be used as relevant biomarkers for chemotherapy outcomes. This can potentially be used to guide clinical treatment decisions.